Dynamic Simulation on Deflagration of LNG Spill - Biao Sun; Kaihua Guo; Vishnu K. Pareek (Journal of Combustion)
The deflagration characteristics of premixed LNG vapour-air mixtures with different mixing ratios were quantitatively and qualitatively investigated by using CFD (computational fluid dynamics) method. The CFD model was initially established based on theoretical analysis and then validated by a lab-scale deflagration experiment. The flame propagation behaviour, pressure-time history, and flame speed were compared with the experimental data, upon which a good agreement was achieved. A large-scale deflagration fire during LNG bunkering process was conducted using the model to investigate the flame development and overpressure effects. Mesh independence and time scale were tested in order to obtain the suitable grid resolution and time step. Deflagration cases with two different LNG vapour volume fractions, i.e., 10.4% and 15.0%, were simulated and compared. The one with a volume fraction of 10.4% which was around stoichiometric mixing ratio had the highest flame propagating speed. High flame velocity observed in the simulation was coupled with the thin flame front where overpressure occurred. The CFD model could capture the main features of deflagration combustion and account for LNG fire hazard which could provide an in-depth insight when dealing with complicated cases.